Pengaruh Stres Kerja dan Pemberian Insentif Terhadap Turnover Intention Karyawan : Survey Pada Rumah Sakit di Gowa - Rasyid Rahman; Darwis, Muhammad Irwan; Stambul, Muh. Idrus (Insan Cita Bongaya Research Journal, 2024)
This research aims to examine and analyze the influence of work stress and incentives on employee turnover intention at Yapika Gowa General Hospital. The type of research used in this research is quantitative research. The sample in this study was 65 respondents. This research uses multiple linear regression analysis techniques with the help of the SPSS program and data obtained from questionnaires distributed to employees of the Yapika Gowa General Hospital. The results of this research show that partially Job Stress has a significant positive effect on Turnover Intention and the Incentive variable has a negative effect on Turnover Intention at the Yapika Gowa General Hospital.